Impact of subnational migration flows on population distribution in Kenya: Analysis using census data - Muyonga, Mary; Otieno , Alfred; Odipo, George (African Human Mobility Review, 2021)
In Kenya, internal migration continues to impact population redistribution, although few studies have looked at subnational variations of the intensities and their overall impact to this process. This study seeks to analyse subnational migration flows and their impact on population redistribution in Kenya. The study uses 1999 and 2009 census micro data to generate migration intensities for each county and map these using ARCGIS software, to show the distributional effects of migration on population for the period of investigation.The findings confirm a shift in the migration patterns in the country over the ten-year period, and the effect on population redistribution in the country. There are wide county variations with net gainers, net losers, and emergence of inactive migration zones. Migrants are concentrated in counties with large, urbanised areas, although suburbanisation is emerging as secondary cities and urban areas attract migrants. Results from the spatial analysis shows that migration intensities are clustered such that neighbouring regions exhibit similar intensities, and two hotspots are visible, a high-high hotspot in Nairobi and Vihiga, and clustering of low intensities in Mombasa and adjacent counties. We conclude that while internal migration effectively contributes to population redistribution, the effect is waning as more regions become urbanised.